2013
DOI: 10.1111/isj.12020
|View full text |Cite
|
Sign up to set email alerts
|

Digitally enabling social networks: resolving IT–culture conflict

Abstract: Digitally enabled social networks, encompassing social media applications such as wikis, blogs and social networking sites, have the potential to dramatically change organizational culture by building communities, promoting information sharing and fostering collaboration. Although organizational social media site (hereinafter SMS) implementations are proliferating, these technologies often do not harmoniously combine with traditional organizational cultures. To shed light on social media's impact on organizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
69
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(77 citation statements)
references
References 45 publications
3
69
0
Order By: Relevance
“…Up until 2015, about eight studies analysed the negative stigma attached to using social media at the workplace (for instance, Koch et al 2013). While a couple of studies also revealed the positive side of social media (for instance, Lu et al 2015), most were seen discussing its ill-effects on work outputs, routine performance, and clash of notions in the personal and professional space (for instance, Ali-Hassan et al 2015).…”
Section: Evolution Of Social Media Research In the Is Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…Up until 2015, about eight studies analysed the negative stigma attached to using social media at the workplace (for instance, Koch et al 2013). While a couple of studies also revealed the positive side of social media (for instance, Lu et al 2015), most were seen discussing its ill-effects on work outputs, routine performance, and clash of notions in the personal and professional space (for instance, Ali-Hassan et al 2015).…”
Section: Evolution Of Social Media Research In the Is Literaturementioning
confidence: 99%
“…In a contrasting case, Cao et al (2015) suggest that social media has the potential to build employees' social capital to positively influence their knowledge integration. In discussing the impact of social media on organizational life, Koch et al (2013) find that conflicts can stem between workplace values and the values these employees ascribe to social media.…”
Section: Negative Stigma Attached To Social Media Usementioning
confidence: 99%
See 1 more Smart Citation
“…Another area of interest relates to how ESN impact the interplay between single organisational sub-cultures [55]. Kuegler et al call for the evaluation of organisational climate and further determinants of the ESN implementation process [56].…”
Section: Cultural Effectsmentioning
confidence: 99%
“…Koch and Gonzalez [14] describe this internal tension within a single organization which they call an IT-culture conflict. Brady [15] found that adopting IT-driven applications change processes, roles, and requisite IT knowledge both among marketers and marketing managers.…”
Section: It Role In Organizational Controlmentioning
confidence: 99%